2009
DOI: 10.1242/jcs.049023
|View full text |Cite
|
Sign up to set email alerts
|

Nicotiana tabacumTTG1 contributes to ParA1-induced signalling and cell death in leaf trichomes

Abstract: suggesting the importance of H 2 O 2 in the pathway of HCD signal transduction from the trichomes to mesophylls. This pathway was no longer activated when leaf trichomes were treated with C51S, a ParA1 mutant protein defective in its interaction with N. tabacum TTG1 (NtTTG1), which is a trichome protein that binds ParA1, rather than C51S, in vitro and in trichome cells. The ParA1-NtTTG1 interaction and the HCD pathway were also abrogated when NtTTG1 was silenced in the trichomes. These observations suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 98 publications
0
62
0
Order By: Relevance
“…As the WD40 domain has multiple modes for recruiting different substrates, WD40-containing proteins can serve as interchangeable substrate receptors and interact with diverse types of proteins (Xu and Min, 2011). Due to this characteristic, WD40-containing TTG proteins are potential regulators of both plant development and defence pathways (Bouyer et al, 2008;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As the WD40 domain has multiple modes for recruiting different substrates, WD40-containing proteins can serve as interchangeable substrate receptors and interact with diverse types of proteins (Xu and Min, 2011). Due to this characteristic, WD40-containing TTG proteins are potential regulators of both plant development and defence pathways (Bouyer et al, 2008;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, for instance, AtTTG1 interacts with the bHLH transcription factor GL3 while recruiting MYB GL1, thereby forming the WD40-bHLH-MYB complex that acts to regulate trichome development (Morohashi et al, 2007;Szymanski et al, 2000;Zhao et al, 2008). Our previous study showed that WD40 enabled tobacco (Nicotiana tabacum) NtTTG1 to interact with ParA1 (Wang et al, 2009), an elicitin protein that is produced by an oomycete pathogen and induces hypersensitive cell death (HCD) in the plant (Kamoun et al, 1993;Liang et al, 2004). The NtTTG1-ParA1 interaction was essential for the induction of HCD in leaf trichomes (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The petunia An11, pomegranate (Punica granatum) WD40, Medicago truncatula WD40-1, and maize PAC1 genes, encoding WD-repeat proteins, all control anthocyanin pigmentation and do not regulate trichome development, but they can complement Arabidopsis ttg1 mutant defect in trichomes (de Vetten et al, 1997;Carey et al, 2004;Pang et al, 2009;Ben-Simhon et al, 2011). In addition, the tobacco NtTTG1 protein, a trichome protein with a high degree of sequence identity to AtTTG1, plays an essential role in hypersensitive cell death signal transduction from leaf trichomes to mesophyll cells (Glover et al, 1998;Wang et al, 2009). However, NtTTG2, a paralog of NtTTG1, not only plays a role in suppressing SA/NPR1-regulated defense against pathogens but also regulates development by affecting the expression of ARF genes (Li et al, 2012;Zhu et al, 2013).…”
Section: Csttg1 Has Both Conserved and Divergent Functions Compared Wmentioning
confidence: 99%